Temperature imaging apparatus and method of manufacturing the same

By introducing a composite of polyallylamine between the poly-10,12-25CDiynylic acid layers, a temperature imaging device is manufactured, which solves the problem of difficulty in achieving large-area temperature imaging in the prior art, and realizes the problem of achieving large-area temperature imaging. Effective temperature imaging and thermal damage protection over a wide temperature range.

CN119497588APending Publication Date: 2025-02-21KEIO UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380054932.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-30
Filing Date
2023-04-28
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively achieve large-area temperature imaging in medical environments, especially to prevent thermal damage when using electric scalpels.

Method used

By introducing a composite of polyallylamine between layers of poly-10,12-25CDiynoic acid, a temperature imaging device can be made that can perform temperature imaging over a wide temperature range and by spraying methods Coat evenly on the substrate.

Benefits of technology

Temperature imaging over a wide temperature range is achieved, providing a large-area temperature imaging device that is easy to manufacture and apply, which can effectively prevent thermal damage in a medical environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497588A_ABST
    Figure CN119497588A_ABST
Patent Text Reader

Abstract

Provided is a temperature imaging device capable of visualizing temperature changes by color even in a large area. The temperature imaging apparatus includes: a substrate; the present invention relates to a substrate comprising a layer of poly-10, 12-pentacosadiynoic acid, a layer of poly-10, 12-pentacosadiynoic acid, and a composite having a polyallylamine introduced between layers of poly-10, 12-pentacosadiynoic acid, the composite being incorporated into or adhered to the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a temperature imaging device and a method for manufacturing the device. Background Art

[0002] Surgeons are concerned about thermal damage to surrounding organs when using electric scalpels while performing their duties. Temperature imaging can be performed by infrared thermography, but because higher accuracy is required in temperature measurement and imaging, more expensive equipment is required. In addition, it is not easy to always have such equipment ready in a medical environment where electric scalpels are used.

[0003] As a temperature indicator patch having a relatively simple configuration, there is disclosed a temperature indicator patch containing a transparent resin and a thermochromic pigment whose color development temperature is 80° C. to 110° C. (Patent Document 1).

[0004] The inventors of the present invention have studied layered polydiacetylene (PDA) that exhibits a color change in response to temperature. PDA is a polymer that exhibits a color change from blue to red in response to an external stimulus. It is known that temperature responsiveness can be adjusted by embedding various chemical species (guests) between layers of a layered structure of 10,12-pentacosadiynoic acid (PCDA), which is a type of PDA. It has been confirmed that, by inserting metal ions between PDA layers (non-patent document 1), a temperature-responsive color change is induced in a color different from the color change of PDA. In addition, it has been confirmed that, by embedding alkylamines (non-patent document 2) or dialkylamines (non-patent document 3) between PDA layers, the temperature range showing the reversibility of the color change is widened according to the increase in the number of carbon atoms of the embedded amine.

[0005] In recent years, the inventors of the present invention have found that when polyallylamine is compounded between layers, the color gradually changes depending on the temperature between about room temperature and 100° C., and thus enables temperature imaging in a wide temperature range (Non-Patent Document 4). However, the guest compound sample has been a powder sample, or it has been difficult to manufacture a temperature imaging device having a large area according to the coating method for a substrate in the prior art.

[0006] Reference List Patent Literature Patent document 1: JP6801878B2 Non-patent literature Non-patent document 1: M. Okaniwa, et al. Adv. Funct. Mater., 2016, 26, 3463-3471 Non-patent document 2: M. Takeuchi, et al. ACS Appl. Mater. Interfaces, 2017, 9, 16546-16552 Non-patent document 3: Y. Oaki, Y. Ishijima, H. Imai, Polymer Journal, 2018, 50, 319-326 Non-Patent Document 4: Aya Edagawa, Hiroaki Imai, and Yuya Oaki, "Lowering the temperature and increasing the width of temperature-responsive color change by controlling the flexibility of layered polydiacetylene," 70th Annual Meeting of the Polymer Science Society of Japan. Summary of the invention

[0007] Technical issues The object of the present invention is to provide a temperature imaging device and a method for manufacturing the device, wherein the temperature imaging device includes a composite in or on a substrate, the composite having polyallylamine introduced between layers of polydiacetylene, and the temperature imaging device can even realize a large-capacity device.

[0008] Technical solution to the problem The present invention includes the embodiments described below.

[0009] Item 1. A temperature imaging device includes: a substrate; and a composite having polyallylamine introduced between layers of poly-10,12-pentacosadiynoic acid, the composite being incorporated into or attached to the substrate.

[0010] Item 2. A temperature imaging device according to item 1, wherein an initial value of red intensity x of the temperature imaging device before heating is 0.280 or greater, and a value of a change Δx of the red intensity x when a color change is caused by heating to 100°C is 0.025 or greater.

[0011] Item 3. A temperature imaging device comprises: a substrate; and a composite of poly-10,12-pentacosadiynoic acid, polyallylamine and an amine compound, the composite being incorporated into or attached to the substrate, wherein at least a portion of the polyallylamine and / or the amine compound is introduced between layers of the poly-10,12-pentacosadiynoic acid.

[0012] Item 4. The temperature imaging device according to item 1 or 3, wherein the plurality of droplets of the composite are attached to the substrate in a dispersed state in a substantially spherical shape.

[0013] Item 5. The temperature imaging device according to item 1 or 3, wherein the substrate is sheet-shaped, and wherein the temperature imaging device is a sheet-shaped device.

[0014] Item 6. The temperature imaging device according to item 1 or 3, wherein the substrate comprises a woven fabric or a non-woven fabric.

[0015] Item 7. The temperature imaging apparatus according to Item 1, wherein the substrate is a sheet-like substrate having a length of 100 mm or more and a width of 100 mm or more.

[0016] Item 8. The temperature imaging device according to item 1, wherein the temperature imaging device has a color change start temperature lower than 30°C and a color change end temperature higher than 80°C.

[0017] Item 9. A method for estimating the specific heat of a liquid, the method comprising: heating the sealed container containing the liquid to a certain temperature; measuring a color change of the temperature imaging device of item 1 or 3 attached to the container; calculating a specific heat equivalent value of the liquid based on a time period from the start of heating until the color change stops and an amount of change Δx of the red intensity x of the temperature imaging device from the start of heating until the color change stops; and The specific heat equivalent value of the liquid is substituted into a function formula of specific heat and specific heat equivalent value to calculate the specific heat of the liquid.

[0018] Item 10. A method for checking temperature changes at a test site, the method comprising: placing the temperature imaging device of item 1 or 3 on the test site; and A color change of the temperature imaging device disposed on the test site after heating is detected.

[0019] Item 11. The method according to item 10, wherein detecting the color change comprises: detecting the color change of the temperature imaging device arranged on or near the affected part subjected to the heating treatment after heating with the energy device used for surgery.

[0020] Item 12. An energy device for surgery, the energy device comprising: a coating attached to the energy device, the coating comprising a composite having polyallylamine introduced between layers of poly-10,12-pentacosadiynoic acid.

[0021] Item 13. An energy device for surgery, the energy device comprising: a coating, the coating being attached to the energy device, the coating comprising a composite containing poly-10,12-pentacosadiynoic acid, polyallylamine and an amine compound, the composite having at least a portion of the polyallylamine and / or the amine compound introduced between layers of the poly-10,12-pentacosadiynoic acid.

[0022] Item 14. A method for manufacturing a temperature imaging device, the method comprising: applying a composition containing 10,12-pentacosadiynoic acid, a polyallylamine having a unit represented by the following general formula (1), and a solvent to a substrate by spraying; removing the solvent; and The 10,12-pentacosadiynoic acid is polymerized to form a composite having the polyallylamine incorporated between layers of poly-10,12-pentacosadiynoic acid:

[0023] Here, n represents an integer.

[0024] Item 15. A method for manufacturing a temperature imaging device, the method comprising: applying a composition containing 10,12-pentacosadiynoic acid, polyallylamine having a unit represented by the following general formula (1), an amine compound, and a solvent to a substrate by spraying; removing the solvent; and polymerizing 10,12-pentacosadiynoic acid to form a composite having at least a portion of the polyallylamine and / or the amine compound incorporated between layers of poly-10,12-pentacosadiynoic acid:

[0025] Here, n represents an integer.

[0026] Item 16. The method according to item 14 or 15, wherein forming the composite comprises: forming the composite so that the composite is attached to the substrate in a substantially spherical shape.

[0027] Advantageous Effects of the Invention According to the temperature imaging device of the present invention, temperature imaging can be performed in a wide temperature range. In addition, according to the manufacturing method of the temperature imaging device of the present invention, a temperature imaging device capable of performing temperature imaging in a wide temperature range can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The formation of a lamellar polymer with 10,12-pentacosadiynoic acid is shown. Figure 1 (A) shows 10,12-pentacosadiynoic acid (PCDA). Figure 1 (B) shows the formation of a layered structure with PCDA. Figure 1 (C) shows the formation of PDA polymer by topochemical polymerization. Figure 1 (D) shows the formation of a composite with a polymer guest introduced between the layers of PDA.

[0029] Figure 2 is a schematic view of a temperature imaging device according to one embodiment.

[0030] Figure 3 (A) shows the XRD patterns of PCDA crystals and PCDA / alkyl polymer guests PEI, PVAm, and PAAm. Figure 3 (B) shows the IR spectra of PCDA crystals and PCDA / alkyl polymer guests.

[0031] Figure 4 (A) shows the XRD patterns of PCDA crystals and PCDA / pyridine polymer guests PVP2 and PVP4. Figure 4 (B) shows the IR spectra of PCDA crystals and PCDA / pyridine polymer guests.

[0032] Figure 5 Photographs of PCDA and PCDA / polymer guest after UV irradiation are shown. Figure 5 (A) shows PDA (polymerized PCDA). Figure 5 (B) shows PDA / PEI. Figure 5 (C) shows PDA / PVAm. Figure 5 (D) shows PDA / PAAm. Figure 5 (E) shows PDA / PVP4. Figure 5 (F) shows PDA / PVP2.

[0033] Figure 6 The change in the peak intensity ratio of the corresponding complex with respect to the UV irradiation time, ie, the polymerization rate, is shown.

[0034] Figure 7Photographs of the color changes of PDA and PDA / alkyl polymer guests are shown.

[0035] Figure 8 The image analysis results of the color change photographs of PDA and PDA / alkyl polymer guests are shown. Figure 8 (A) is the chromaticity diagram. Figure 8 (B) shows the temperature-dependent change of the distance between the measurement starting point and the corresponding plot.

[0036] Fig. 9 UV-Visible spectra are shown. Fig. 9 (A) shows the PDA. Fig. 9 (B) shows PDA / PAAm.

[0037] Fig.10 (A) shows the torsion angle of the conjugated chain of PDA. Fig.10 (B) shows the torsion angle of the conjugated chain of PDA / PAAm.

[0038] Fig.11 DSC measurement results of PDA and PDA / alkyl-based polymer guests are shown.

[0039] Fig.12 Optical microscope images of samples each produced by the LbL method are shown. Fig.12 (A) shows PDA / PEI. Fig.12 (B) shows PDA / PVAm. Fig.12 (C) shows PDA / PAAm.

[0040] Fig.13 Shown are SEM images of samples each manufactured by the LbL method. Fig.13 (A) shows PDA / PEI. Fig.13 (B) shows PDA / PVAm. Fig.13 (C) shows PDA / PAAm.

[0041] Fig.14 Comparisons between silk cloths coated by various coating methods are shown. Fig.14 (A) is a picture taken with a camera for the layer-by-layer method (LbL method). Fig.14 (B) is a photo taken with a camera for the direct synthesis method. Fig.14 (C) is a photograph taken with a camera for the spraying method. Fig.14 (D) is an optical micrograph for the LbL method. Fig.14 (E) is an optical micrograph for the direct synthesis method. Fig.14(F) is an optical micrograph for the spray coating method.

[0042] Fig.15 are photographs of PDA and PDA / polymer guest applied to a PMMA substrate by spray coating. Fig.15 (A) shows the PDA. Fig.15 (B) shows PDA / PEI. Fig.15 (C) shows PDA / PVAm. Fig.15 (D) shows PDA / PAAm.

[0043] Fig.16 are SEM images of PDA and PDA / polymer guest applied to PMMA substrates by spray coating. Fig.16 (A) shows the PDA. Fig.16 (B) shows PDA / PEI. Fig.16 (C) shows PDA / PVAm. Fig.16 (D) shows PDA / PAAm.

[0044] Fig.17 The relationship between the specific heat equivalent value and the specific heat of the literature value is shown. (a) represents silicone oil, (b) represents ethanol, (c) represents water, and (d) represents a 50 wt% ethanol aqueous solution.

[0045] Fig.18 This is a photograph of a temperature imaging sheet attached to a piece of pork before heat treatment with an electric scalpel.

[0046] Fig.19 (A) is a photograph of a silk cloth coated with PDA / PAAm which is placed on a piece of meat and then cut with an electric scalpel A. Fig.19 (B) is a photograph of the silk cloth coated with PDA / PAAm which is placed on the piece of meat and then cut with an electric scalpel B. Fig.19 (C) is a graph showing the relationship between the distance from the cutting portion of the piece of meat (horizontal axis) and the red intensity (x, left axis) and temperature (right axis) of the device when using the electric scalpel A and the electric scalpel B.

[0047] Fig. 20 Each shows a quantitative analysis of the color change behavior of the PAAm / PDA-guest complex based on image analysis. The vertical axis represents the red intensity change Δx determined by image analysis. Fig. 20 (A) shows the color change of the composite containing PAAm with corresponding introduced amounts when the temperature increases. Fig. 20 (B) shows the color change of the composites containing PAAm at corresponding introduced amounts upon cooling.

[0048] Fig.21 Quantitative analysis of the color change behavior of the PAAm / PDA-guest complex based on image analysis is shown. The vertical axis represents the red intensity change Δx determined by image analysis. Solid line: color change of the complex containing three amounts of pXy when the temperature is increased, dotted line: color change of the complex containing three amounts of pXy when cooling.

[0049] Fig. 22 FT-IR measurement results of Samples I to V of the composites are shown.

[0050] Fig.23 RGB image analysis results of sample II (A), sample III (B), and sample IV (C) of the composite are shown.

[0051] Fig.24 is a SEM image. Fig.24 (A) is the secondary electron image of PDA-p-Xy. Fig.24 (B) is the secondary electron image of PAAm / PDA-p-Xy. Fig.24 (C) is the backscattered electron image of PDA-p-Xy. Fig.24 (D) is the backscattered electron image of PAAm / PDA-p-Xy.

[0052] Fig.25 is a schematic view of the phase separation structure of PAAm and PDA-p-Xy.

[0053] Fig.26 PAAm / PCDA-guest and PCDA-guest are shown. Fig.26 (A) shows the IR measurement results. Fig.26 (B) shows the XRD measurement results.

[0054] Fig. 27 are optical micrographs of the color change behaviors of PAAm / PDA-guest and PDA-guest.

[0055] Fig.28 PAAm / PDA-p-Xy-PAAm coating of filter paper substrates and silk cloth substrates using three coating methods are shown.

[0056] Fig.29 Optical images of the substrate before coating (left) and after PAAm / PDA-p-Xy coating and polymerization (right). Fig.29 (A) shows polyurethane. Fig.29 (B) shows hard polyethylene. Fig.29 (C) shows polypropylene. Fig.29(D) shows a silk cloth. Fig.29 (E) shows polyethylene fibers. Fig.29 (F) shows polystyrene.

[0057] Fig.30 The color change behavior of the PAAm / PDA-p-Xy silk cloth substrate is shown.

[0058] Fig.31 Image analysis results of the color change behavior of the PAAm / PDA-p-Xy silk cloth substrate are shown. DETAILED DESCRIPTION

[0059] A first embodiment of the present invention is described in detail.

[0060] 10,12-pentacosadiynoic acid (PCDA, represented by reference numeral 1), which is a diacetylene (DA), is an amphiphilic molecule having a carboxyl group at its terminal end ( Figure 1 (A)), and form a layered structure by self-assembly ( Figure 1 (B)). PCDA has a molecular length of 3.18 nm and is arranged with a molecular tilt of about 45° to about 50°, thus having an interlayer spacing of 4.61 nm. Topological chemical polymerization was performed by UV irradiation and heating ( Figure 1 (C)) is carried out to exhibit blue. PDA obtained by polymerization of PCDA exhibits an irreversible color change from blue to red when heated to about 65°C. Polymerized PCDA is sometimes referred to as "PDA" hereinafter.

[0061] It is known that temperature-responsive color change can be controlled by forming a composite with various guests introduced between layers of PCDA. When the interlayer guests each have a low molecular weight, the guests are aligned between the layers of PCDA without any gap by van der Waals force, and thus the alignment characteristics and the ease of polymerization increase, although the flexibility of the layer structure is low. When the interlayer guests each have a high molecular weight, the crystallinity decreases due to the mobility of the polymer chain, and thus the alignment characteristics and the ease of polymerization decrease, although the flexibility of the layer structure is high.

[0062] In this study, we prepared a novel nanostructured carbon nanotube with a specific polymer guest ( Figure 1 The composite of (D, represented by reference numeral 2) and the polymer prepared therefrom to increase the flexibility of the layer structure have been successful in expanding the control range of thermal stimulus responsiveness.

[0063] Specifically, for example, the degree of polymerization or color change in the case of using each of the following five polymer guests (I) to (V) as an interlayer guest for the PCDA layer was observed. As a result, it was found that the polymerization rate was low in the composite containing the pyridine guest (i.e., poly(4-vinylpyridine) (IV) or poly(2-vinylpyridine) (V)), and the polymerization was sufficiently carried out in the composite containing the alkyl guest (i.e., polyethyleneimine (I), polyethyleneamine (II) or polyallylamine (III)). In addition, it was found that in each composite containing the alkyl guest between the layers of poly-PCDA (PDA), the color change start temperature was lowered and the color change temperature width was increased compared to those of the PCDA polymer (PDA) without any guest, and as the guest polymer became more and more bulky in the order of polyethyleneimine (I), polyethyleneamine (II) and polyallylamine (III), the color change temperature was further lowered and the width was further increased. In particular, the composite of poly-PCDA (PDA) and polyallylamine (III) has a color change start temperature of -50°C, a color change end temperature of 220°C, and a color change temperature width of 270°C, and thus within the actual temperature range of 0°C to 100°C, the color change is so clear that it can be observed with the naked eye.

[0064]

[0065] More surprisingly, in order to increase the area of ​​a temperature imaging device having a composite of polyallylamine introduced between layers of poly-PCDA (PDA), a PCDA composite prepared using each of the five polymer guests (I) to (V) mentioned above was applied to a large-area substrate by spray coating, wherein the two-dimensional (length × width) dimensions of the surface to which the composite was applied were 1 cm or more, respectively. As a result, only the composite containing polyallylamine (III) achieved uniform coating.

[0066] Therefore, in the temperature imaging device of the first embodiment of the present invention, polyallylamine (III) is used as the guest polymer.

[0067] A temperature imaging device according to a first embodiment of the present invention includes: a substrate; and a composite having polyallylamine introduced between layers of poly-10,12-pentacosadiynoic acid, the composite being incorporated into or attached to the substrate. Figure 2 One embodiment of a temperature imaging device 10 is illustrated in FIG. 1 , and the temperature imaging device 10 includes a substrate 11 having a flat plate shape and a composite 12 attached to the substrate 11 .

[0068] The polyallylamine is a polyallylamine having a unit represented by the following general formula (1):

[0069] Here, n represents an integer.

[0070] The number average molecular weight of the polyallylamine having the unit represented by the general formula (1) is preferably from 10,000 to 20,000.

[0071] In some embodiments, in the temperature imaging device, the particle diameter of the complex can be observed with, for example, an electron microscope, and the complex can have, for example, a diameter of 1 μm to 10 μm. The average particle diameter of a complex having a substantially spherical shape can also be measured, and complexes each having a diameter of 1 μm or greater observed with, for example, an electron microscope are randomly selected, and the diameters of 20 or more complexes are measured. The average particle diameter can be 1 μm to 10 μm.

[0072] The type of substrate is not particularly limited, and embodiments thereof include: synthetic resins such as thermoplastic resins and thermosetting resins; elastomers such as thermoplastic elastomers and thermosetting elastomers; rubber; metal; paper; and fabrics of natural materials and synthetic materials. The fabrics include woven fabrics and non-woven fabrics. Embodiments of natural materials include, but are not limited to, cotton and silk. Embodiments of synthetic materials include, but are not limited to, synthetic resins such as polyesters, polyolefins, and polyurethanes.

[0073] In some embodiments, from the perspective of the ease of attachment of the composite with polyallylamine introduced between the layers of polydiacetylene to the substrate, the substrate is preferably a woven fabric or a non-woven fabric. Compared with the particle size of the composite using a guest polymer other than polyallylamine, the particle size of the composite of the embodiment of the present invention is reduced, and thus small particles are easily attached to the fiber material for the woven fabric or the non-woven fabric. Therefore, uniform coating can be achieved. Therefore, the composite is also suitable for large-area coating.

[0074] The shape of the substrate is not particularly limited, but is, for example, in the form of a sheet. The substrate may be a flat plate-shaped sheet, or may be a sheet having a curved surface.

[0075] The size of the substrate is not particularly limited, but the two-dimensional size of the surface of the substrate to which the composite having polyallylamine introduced between the layers of polydiacetylene is applied is preferably 1 mm to 100 cm×1 mm to 100 cm square, more preferably 1 cm to 100 cm×1 cm to 100 cm square, and when the substrate has a large area, the size is 10 cm to 100 cm×10 cm to 100 cm square. The ratio between the respective two-dimensional sizes is preferably 100:1 to 1:100, more preferably 10:1 to 1:10.

[0076] When the substrate is a sheet-like substrate, the size of the substrate is not particularly limited, but is, for example, 1 mm to 100 cm in length and 1 mm to 100 cm in width, preferably 1 cm to 100 cm in length and 1 cm to 100 cm in width, and when the substrate has a large area, the size is 10 cm to 100 cm in length and 10 cm to 100 cm in width. The ratio "length: width" is preferably 100:1 to 1:100, more preferably 10:1 to 1:10. The thickness is not particularly limited, but is preferably smaller than the length and width.

[0077] When the temperature imaging device is a temperature imaging sheet having a large area, the two-dimensional dimensions of the length and the width of each of the substrate and the temperature imaging sheet are each preferably larger than 10 cm.

[0078] In the temperature imaging device, part or all of the substrate may be surrounded by a transparent film as long as heat transfer to the composite having polyallylamine introduced between the layers of poly-10,12-pentacosadiynoic acid is not prevented. The thickness of the film is not particularly limited, and is preferably 200 μm or less. When the substrate is surrounded by such a film, waterproof properties and / or antifouling properties can be imparted to the substrate while enabling observation of color changes of the temperature imaging device.

[0079] The temperature imaging device of the first embodiment of the present invention has a wide color change temperature range when the temperature is increased using a heating device. The color change of the temperature imaging device of the first embodiment of the present invention can be directly observed with the naked eye, or can be photographed to form an image and provided as numerical data.

[0080] The color change start temperature of the temperature imaging device of the first embodiment of the present invention is preferably lower than 40°C, lower than 30°C, lower than 20°C, lower than 10°C, or lower than 0°C. The color change start temperature of the temperature imaging device of the first embodiment of the present invention is more preferably lower than 30°C. When the color change starts within such a temperature range, the color change can be detected at a temperature lower than room temperature or body temperature. In addition, the color change end temperature of the temperature imaging device of the first embodiment of the present invention is preferably higher than 60°C, higher than 70°C, higher than 80°C, higher than 90°C, or higher than 100°C. When the color change ends within such a temperature range, a color change accompanying a temperature increase to an actual temperature (such as a temperature at which proteins are denatured or a temperature lower than the boiling point of water) can be detected.

[0081] In some embodiments, the color change start temperature of the temperature imaging device is lower than 30° C., and its color change end temperature is higher than 80° C. In such a temperature range, color changes at temperatures including daily life temperature, subject's body temperature, and the denaturation temperature of protein can be detected.

[0082] In some embodiments, the color change occurs over the entire range of at least 30°C to 80°C. In such a temperature range, the color change caused by thermal stimulation can be detected over a wide range including the temperature of daily life, the body temperature of a subject, and the denaturation temperature of a protein. In some embodiments, the color change occurs over the entire range of at least 20°C to 100°C. In some embodiments, the color change occurs over the entire range of at least 0°C to 100°C.

[0083] In the temperature imaging device of the first embodiment of the present invention, when the color change of the temperature imaging device before heating and after heating to 100°C by temperature increase is image analyzed, the initial value of the red intensity x before heating is represented by x0, the red intensity after heating to 100°C is represented by x1, and the amount of change in the red intensity caused by heating is represented by Δx=x1-x0, the initial value x0 of the red intensity x before heating is preferably 0.280 or more, and the value of the amount of change Δx of the red intensity x when the color change is caused by heating to 100°C is preferably 0.025 or more. The temperature when the initial value x0 of the red intensity x before heating is measured is preferably 20°C. The red intensity x can be calculated according to x=X / (X+Y+Z) by calculating R, G, and B values ​​from the image of the temperature imaging device with software (ImageJ) and converting the R, G, and B values ​​into an XYZ color system using the Rec.709 standard. When the value of the change amount Δx of the red intensity x is 0.025 or more, the color density of the temperature imaging device is easily viewed, and the change amount Δx of the red intensity x when the color change is caused by heating to 100° C. is large. Therefore, such a temperature imaging device is suitable for detecting the color change caused by heating.

[0084] The temperature imaging device of the first embodiment of the present invention can be used for various applications that require detection of temperature changes. For example, an energy device for surgery (such as an electric scalpel) used during surgery may cause thermal damage around the affected part that requires treatment, but the temperature imaging device of the first embodiment of the present invention can be directly installed near the affected part, and thus the temperature near the affected part and its temperature changes caused by the treatment can be visualized by color. The temperature imaging device of the first embodiment of the present invention is particularly useful because the color change can be from close to body temperature to about 80°C. Therefore, the temperature distribution around the energy device used for surgery can be visualized and quantified, and thus it can be identified at a glance which operations or usage history may cause risks, resulting in the use and development of safe or secure surgery or safe and secure medical devices.

[0085] The temperature imaging device of the first embodiment of the present invention can be used, for example, to examine or detect temperature changes at or near a test site of a subject. The subject may be a living body such as a human being or may be a non-living body.

[0086] In some embodiments, a method for checking temperature changes at a test site includes: arranging a temperature imaging device of the first embodiment of the present invention at the test site; and detecting a color change of the temperature imaging device arranged at the test site after heating. The term "test site" refers to a site or its vicinity that has been subjected to a heat treatment. The term "near the site subjected to a heat treatment" refers, for example, to an area from the site subjected to a heat treatment to a position 5 cm away from it, preferably to an area from the site subjected to a heat treatment to a position 3 cm away from it, and more preferably to an area from the site subjected to a heat treatment to a position 1 cm away from it. The vicinity of the site subjected to a heat treatment may be a position adjacent to the site subjected to a heat treatment. The temperature imaging device is particularly preferably a temperature imaging sheet.

[0087] In some embodiments, the method for checking the temperature change of the test site is a method for checking the temperature change near the site (e.g., the affected part) subjected to the heating treatment, the method comprising: arranging the temperature imaging device mentioned above of the first embodiment of the present invention near a certain site; and detecting the color change of the temperature imaging device arranged near the site after the site is subjected to the heating treatment. The temperature imaging device is particularly preferably a temperature imaging sheet.

[0088] Examples of heating devices include: energy devices used for surgery, such as electric scalpels; and heaters. The term "near the site treated with heat" refers to, for example, an area from the site treated with heat to a position 5 cm away from it, preferably an area from the site treated with heat to a position 3 cm away from it, and more preferably an area from the site treated with heat to a position 1 cm away from it. The area near the site treated with heat may be a position adjacent to the site treated with heat.

[0089] In some embodiments, the temperature imaging sheet can be cut into the required size and used on site when necessary. For example, when a doctor manipulates an electric scalpel, through the color change of the temperature imaging sheet of the first embodiment of the present invention, it is possible to view in real time how far the heat is conducted around the part where the electric scalpel is used or how much heat the main body through which the electric scalpel is reused has. Therefore, the risk of thermal damage to the part or surrounding organs or nerves that have been heated with the electric scalpel can be visually understood. The temperature imaging sheet is also useful for medical equipment manufacturers because the performance or safety of heating equipment (such as electric scalpels) can be visually observed.

[0090] In some embodiments, an energy device for surgery is provided, the energy device comprising: a coating, the coating being attached to the energy device, the coating comprising a composite having polyallylamine introduced between layers of poly-10,12-pentacosadiynoic acid. The term "energy device for surgery" refers to a device that functions as an incision, coagulation and / or hemostasis by releasing energy from microwaves, high-frequency waves or ultrasound waves to allow it to act on a biological target portion. The energy device is suitable for use in surgery. Embodiments of energy devices for surgery include scalpels, pinch forceps, forceps and snares. For example, by incorporating a coating comprising a composite into the body of an electric scalpel as a temperature indicator, it is expected that surgery can be performed while visually monitoring the temperature during use.

[0091] As described above, each of the temperature imaging device of the first embodiment of the present invention and the coating layer attached to the heating device (the coating layer including a composite having polyallylamine introduced between layers of poly-10,12-pentacosadiynoic acid) can completely solve the problem of thermal damage when using the heating device.

[0092] Next, a method for manufacturing the temperature imaging apparatus of the first embodiment of the present invention is described.

[0093] A method for manufacturing a temperature imaging device according to a first embodiment of the present invention includes: applying a solution containing 10,12-pentacosadiynoic acid, polyallylamine having a unit represented by the following general formula (1), and a solvent to a substrate by spraying; removing the solvent; and 10,12-pentacosadiynoic acid is polymerized to form a composite having polyallylamine incorporated between the layers of poly-10,12-pentacosadiynoic acid:

[0094] Here, n represents an integer.

[0095] The number average molecular weight of the polyallylamine having the unit represented by the general formula (1) is preferably from 10,000 to 20,000.

[0096] The solvent of the solution used for spraying is not particularly limited, but is preferably an organic solvent, and examples thereof may include hexane, ethanol, and a mixed solvent thereof.

[0097] The ratio between 10,12-pentacosadiynoic acid and polyallylamine having a unit represented by the following general formula (1) in the solution is not particularly limited as long as a composite having polyallylamine introduced between layers of poly-10,12-pentacosadiynoic acid can be formed, but the molar ratio of the carboxyl group of 10,12-pentacosadiynoic acid to the amino group of polyallylamine is preferably set to 1:2.

[0098] Before applying a solution containing 10,12-pentacosadiynoic acid, polyallylamine having a unit represented by the following general formula (1) and a solvent to a substrate by spraying, the solution is preferably dispersed by ultrasonic waves to miniaturize and homogenize particles of the solute.

[0099] The application of the solution to the substrate is performed by applying the solution to the substrate in an upright state by spraying from a position away from the substrate. The distance between the substrate and the spray orifice of the container containing the solution can be appropriately selected.

[0100] The type and shape of the substrate are as described above.

[0101] The removal of the solvent may be performed by natural drying, or may be performed by forced drying via a known drying technique.

[0102] The polymerization of 10,12-pentacosadiynoic acid can be performed by UV irradiation.There are known topochemical polymerizations of 10,12-pentacosadiynoic acid by UV irradiation.

[0103] In some embodiments, forming a complex includes: forming a complex so that the complex is attached to a substrate in a generally spherical shape. The particle diameter of the complex having a generally spherical shape can be observed with, for example, an electron microscope, and the complex can have, for example, a diameter of 1 μm to 10 μm. The average particle diameter of the complex having a generally spherical shape can also be measured, and complexes each having a diameter of 1 μm or more observed with, for example, an electron microscope are randomly selected, and the diameters of 20 or more complexes are measured. Its average particle diameter can be 1 μm to 10 μm. Those skilled in the art who have read this specification can adjust the particle diameter of the complex having a generally spherical shape attached to the substrate by, for example, selecting the conditions of the ultrasonic treatment to meet the desired range.

[0104] According to the method of manufacturing the temperature imaging device of the first embodiment of the present invention by spray coating, a desired substrate can be coated simply and uniformly, and thus a large-area device can be manufactured.

[0105] Next, the second embodiment of the present invention is described in detail. In the second embodiment of the present invention, the difference from the first embodiment is mainly described.

[0106] In this description, the term "low molecular weight amine" refers to an amine compound having a molecular weight of 600 or less, and preferably refers to an amine compound having a molecular weight of 300 or less. When a molecular formula can be specified, the molecular weight of the low molecular weight amine can be determined based on the molecular formula. When a molecular formula cannot be specified, a number average molecular weight (in terms of polystyrene) measured by gel permeation chromatography (GPC) is used.

[0107] The temperature imaging device of the second embodiment of the present invention includes: a substrate; and a composite of poly-10,12-pentacosadiynoic acid, polyallylamine and a low molecular weight amine, the composite being incorporated into the substrate or attached to the substrate, wherein at least a portion of the polyallylamine and / or the amine compound is introduced between layers of the poly-10,12-pentacosadiynoic acid.

[0108] In the temperature imaging device of the second embodiment of the present invention, polyallylamine and / or an amine compound are used as guest molecules. The molecular weight of the amine compound can be calculated based on the molecular formula. The amine compound is free of polyallylamine.

[0109] The polyallylamine is a polyallylamine having a unit represented by the above general formula (1):

[0110] Here, n represents an integer.

[0111] The number average molecular weight of the polyallylamine having the unit represented by the general formula (1) is preferably from 10,000 to 20,000.

[0112] The low molecular weight amine can be a monoamine, a diamine or a triamine. Examples of low molecular weight amines include, but are not limited to, aromatic amines (monoamines or diamines), aliphatic amines (monoamines or diamines), alicyclic amines (monoamines or diamines) and amino acids.

[0113] Regarding the mixing ratio of PCDA, PAAm and the low molecular weight amine in the composite, when the molar ratio of PCDA is set to 1, it is preferred that the molar ratio of PAAm is 0.1 to 0.9 and the molar ratio of the low molecular weight amine is 0.5 to 5, and more preferably the molar ratio of PAAm is 0.3 to 0.7 and the molar ratio of the low molecular weight amine is 1 to 2.

[0114] In the case of a polymer obtained by adding polyallylamine to PCDA, as described in the temperature imaging device of the first embodiment of the present invention, the color change starting temperature of the composite is lowered and its color change temperature width is increased compared to those of the PCDA polymer without any guest.

[0115] Meanwhile, when a low molecular weight amine is added to PCDA without adding polyallylamine, the color change behavior of polydiacetylene (e.g., the width of the color change temperature and the temperature responsiveness) changes according to the low molecular weight amine. Furthermore, even in the case where polyallylamine is added to PCDA, when the low molecular weight amine is added as a third component, the color change behavior of the low molecular weight amine is exhibited. When the low molecular weight amine is a diamine, the color change may be reversible.

[0116] In a composite of poly-10,12-pentacosadiynoic acid (poly-PCDA), polyallylamine, and a low molecular weight amine, when a large amount of polyallylamine is inserted between layers of poly-PCDA, a temperature imaging device becomes close to the temperature imaging device of the first embodiment of the present invention. When a large amount of low molecular weight amine is inserted between layers of poly-PCDA, phase separation between a portion formed of poly-PCDA and the low molecular weight amine and a portion formed of polyallylamine is likely to occur. According to the second embodiment of the present invention, a composite having both coating properties of poly-PCDA and polyallylamine and reversibility of color change caused by the addition of the low molecular weight amine is achieved, and thus a temperature imaging device including the composite can be manufactured.

[0117] In the composite of poly-PCDA, polyallylamine and low molecular weight amine, as the amount of polyallylamine becomes larger, the color change starting temperature decreases compared to the case where only poly-PCDA and low molecular weight amine are used. In addition, when a diamine is incorporated as the low molecular weight amine, the reversibility of the color change can occur within a certain temperature range starting from the color change starting temperature.

[0118] The color change start temperature, color change end temperature, and color change temperature width of the composite of poly-PCDA, polyallylamine, and a low molecular weight amine can vary depending on the type of the low molecular weight amine. When, for example, p-xylene diamine is used as the low molecular weight amine, the color change start temperature is about 60° C., the color change end temperature is about 150° C., and the color change temperature width is about 90° C. Therefore, within the actual temperature range, the color change is so clear that it can be observed with the naked eye.

[0119] In addition, in the temperature imaging device of the second embodiment, a composite of poly-10,12-pentacosadiynoic acid, polyallylamine and a low molecular weight amine is used, and thus is suitable for increasing the area. When the composite is applied to a large area substrate (where the two-dimensional (length×width) dimensions of the surface to which the composite is applied are 1 cm or more, respectively) by spray coating, uniform coating with the composite can be performed.

[0120] In some embodiments, in the temperature imaging device, the particle diameter of the complex can be observed with, for example, an electron microscope, and the complex can have, for example, a diameter of 1 μm to 10 μm. It is also possible to measure the average particle diameter of a complex having a substantially spherical shape, and randomly select complexes each having a diameter of 1 μm or more observed with, for example, an electron microscope, and measure the diameters of 20 or more complexes. The average particle diameter thereof can be 1 μm to 10 μm.

[0121] The kind of the substrate is as described for the temperature imaging apparatus of the first embodiment. Substrates of various materials can each be used as the substrate.

[0122] In some embodiments, from the perspective of the ease of attachment of the composite to the substrate, the substrate is preferably a woven fabric or a non-woven fabric. Compared with the particle size of the composite using a guest polymer other than polyallylamine, the particle size of the composite of the embodiment of the present invention is reduced, and thus small particles are easily attached to the fiber material of the woven fabric or the non-woven fabric. Therefore, uniform coating can be achieved. Therefore, the composite is also suitable for large-area coating.

[0123] The shape and size of the substrate are also as described for the temperature imaging apparatus of the first embodiment.

[0124] Like the temperature imaging device of the first embodiment, the temperature imaging device of the second embodiment of the present invention has a wide color change temperature range when the temperature is raised by a heating device. The color change of the temperature imaging device of the second embodiment of the present invention can be directly observed with the naked eye, or can be photographed to form an image and provided as numerical data.

[0125] The description of the temperature imaging device of the first embodiment can be applied to the preferred color change start temperature and the preferred color change end temperature of the temperature imaging device of the second embodiment of the present invention, and the temperature can be changed by the low molecular weight amine to be used. In some embodiments, the color change occurs over the entire range of at least 0°C to 100°C.

[0126] The temperature imaging device of the second embodiment of the present invention can also be used for various applications requiring detection of temperature changes, such as a method of examining temperature changes at a test site in the same manner as the temperature imaging device of the first embodiment.

[0127] In some embodiments, an energy device for surgery is provided, the energy device comprising: a coating, the coating being attached to the energy device, the coating comprising a composite containing poly-10,12-pentacosadiynoic acid, polyallylamine and an amine compound, the composite having at least a portion of the polyallylamine and / or amine compound introduced between layers of poly-10,12-pentacosadiynoic acid. An embodiment of the energy device for surgery is as described above.

[0128] As described above, in each of the temperature imaging device of the second embodiment of the present invention and the heating device including a coating attached to the heating device, the coating including a complex of poly-10,12-pentacosadiynoic acid, polyallylamine and a low molecular weight amine can be able to completely solve the problem of thermal damage when using the heating device.

[0129] A method for manufacturing a temperature imaging device according to a second embodiment of the present invention comprises: applying a solution containing 10,12-pentacosadiynoic acid, polyallylamine having a unit represented by the following general formula (1), a low molecular weight amine, and a solvent to a substrate by spraying; removing the solvent; and polymerizing 10,12-pentacosadiynoic acid to form a composite having at least a portion of the polyallylamine and / or amine compound incorporated between layers of poly-10,12-pentacosadiynoic acid:

[0130] Here, n represents an integer.

[0131] The number average molecular weight of the polyallylamine having the unit represented by the general formula (1) is preferably from 10,000 to 20,000.

[0132] The solvent of the solution used for spraying is not particularly limited, but is preferably an organic solvent, and examples thereof may include hexane, ethanol, and a mixed solvent thereof.

[0133] The ratio among PCDA, polyallylamine having a unit represented by the general formula (1) and the low molecular weight amine in the solution is not particularly limited as long as a composite having polyallylamine and / or the low molecular weight amine introduced between the layers of polydiacetylene can be formed, but the molar ratio of the amino group of the low molecular weight amine to the carboxyl group of PCDA is preferably 0.6 to 1.0. Furthermore, the amount of the low molecular weight amine (e.g., p-Xyj) is preferably 0.4 mol or more, and the amount of the polyallylamine is preferably 0.5 mol to 1.5 mol, more preferably 1 mol to 1.3 mol, relative to 1 mol of PCDA.

[0134] Dispersing of the solution, application of the solution to the substrate, kind and shape of the substrate, removal of the solvent, polymerization of 10,12-pentacosadiynoic acid, and shape and size of the composite to be obtained are as described for the method for manufacturing the temperature imaging device of the first embodiment.

[0135] According to the method of manufacturing the temperature imaging device of the second embodiment of the present invention by spray coating, a desired substrate can be coated simply and uniformly, and thus a large-area device can be manufactured.

[0136] The present invention is described in more detail below by way of examples, but the present invention is not limited thereto. In the examples, unless otherwise specified, the term "PCDA" refers to 10,12-pentacosadiynoic acid before polymerization, and the term "PDA" refers to polymerized PCDA.

[0137] Example Test 1 Preparation and evaluation of complexes of PCDA and polymer guests 1. Preparation of PCDA and Polymer Guests (1) Preparation of mixed solutions of PCDA and polymer guest by direct synthesis method 25 mg of PCDA was dissolved in 2.5 ml of ethanol or 5 ml of hexane to produce a PCDA solution. The solution was filtered with a funnel and filter paper to remove the polymer of PCDA. 6.30 mg of polyethyleneimine (PEI, Mw: about 25,000) or 37.4 μl of polyallylamine (PAAm, Mw: about 17,000) was added to the filtered PCDA ethanol solution, and 5.74 mg of polyvinylamine (PVAm, Mw: about 11,000) was added to the PCDA hexane solution so that the ratio "PCDA: guest" was 1:2.

[0138] The PCDA / alkyl polymer guest mixed solution was dispersed with ultrasound for 30 minutes, and then the solution was drop-coated on a glass substrate. The solution was placed in a constant temperature bath at 4°C so that the solvent was volatilized and removed. Thus, a glass substrate device of PCDA / alkyl polymer guest was obtained. The ratio represents the ratio when the number of molecules of PCDA and guest are equal to each other in terms of the monomer unit of the guest.

[0139] (2) Preparation of PCDA / pyridine polymer guest by direct synthesis 16 mg of PCDA was dissolved in 1 ml of acetone to produce a PCDA solution. The solution was filtered using a funnel and filter paper to remove the polymer of PCDA. 414.0 mg of poly(4-vinylpyridine) (PVP4, Mw: about 60,000)) or 215.1 mg of poly(2-vinylpyridine) (PVP2, Mw: about 37,500) was added to the filtered PCDA solution so that the ratio "PCDA: guest" was 1:2.

[0140] 3 ml of ethanol and 2.7 ml of acetone were added to the PCDA / PVP4 or PCDA / PVP2 mixed solution, and 3.7 ml of acetone was added to the PCDA / PVP4 mixed solution. Thereafter, the PCDA / pyridine polymer guest mixed solution was dispersed with ultrasound for 10 minutes until the solution became uniform, and the solution was allowed to stand for 1 day. The next day, 300 μl of the corresponding solution dispersed with ultrasound for 10 minutes was drop-coated on two 2.5 cm square glass substrates located on a cold plate at 40°C. Once the solvent was evaporated, 300 μl of the corresponding solution was drop-coated on the same glass substrate. The process was continued until no solution existed. Thus, a glass substrate device of PCDA / pyridine polymer guest was obtained.

[0141] (3) Preparation of PCDA / alkyl polymer guest by layer-by-layer method (LbL method) Each of 4.73 mg of PEI, 4.29 mg of PVAm, and 28.0 μl of PAAm was dissolved in 5 ml of pure water to produce a guest solution. 18.7 mg of PCDA was dissolved in 5 ml of acetone to produce a host solution. Each of a 0.5 cm square paper substrate and a silicon substrate was immersed in the guest solution for 30 seconds, and then the paper substrate and the silicon substrate were lifted. The excess solution on the back surface and the side surface of the substrate was removed with PROWIPE, and the substrate was naturally dried at room temperature. Next, each of the substrates was washed by rinsing in pure water for 2 to 3 seconds, and then each of the substrates was dried in the same manner. Finally, each of the substrates was immersed in the host solution for 30 seconds, and then each of the substrates was lifted, and each of the substrates was dried in the same manner. The process of immersion, washing, and drying with three solutions was defined as one cycle, and the cycle was repeated six times to provide a paper substrate device and a silicon substrate device of PCDA / alkyl polymer guest.

[0142] The polymer objects of items (1) to (3) were irradiated with UV light and solid-state photopolymerized using a hand lamp (ASONE, Handy UV Lamp SLUV-6, 254 nm) as a light source.

[0143] 2. Evaluation Methodology (1) Observe the color change behavior of the composite in response to heat Regarding the PDA / alkyl polymer guest and the PDA / alkyl low molecular weight guest after polymerization, the color change behavior to heat was observed. The glass substrate on which the sample was drop-coated or the paper substrate coated with the sample was placed on a temperature stage, and heating from -50°C to a maximum of 220°C was performed. The sample was kept at each temperature for 2 minutes, and then the sample was photographed.

[0144] (2) X-ray diffraction (XRD) In order to observe the enlargement of the interlayer distance and the change of the periodic structure caused by the formation of the complex with amine, the X-ray diffraction pattern of the complex with the polymer guest before polymerization was obtained by using X-ray diffraction (Bruker, D8 Advance). The voltage and current values ​​of the X-ray tube bulb were set to 40 kV and 40 mA, respectively, and the measurement was performed by the continuous scanning method with CuKα rays.

[0145] (3) Scanning electron microscopy (SEM) The glass substrate onto which the PCDA / polymer guest was drop-coated and polymerized was fixed to an aluminum stage with a conductive tape. Osmium coating was performed to ensure conductivity. Thereafter, the detailed structure of the sample was observed with a scanning electron microscope (S-2700; Hitachi, Sirion; FEI, JSM-7600F; Jeol).

[0146] (4) Optical microscope The structure of PDA / polymer guest on the silicon substrate was observed using a fluorescence microscope (OLIMPUS, BX51-FL).

[0147] (5) Ultraviolet-visible (UV-Vis) spectroscopy When observing the temperature color change behavior of each of PDA and PDA / PAAm, the measurement was performed by using a glass substrate on which each of PCDA and PCDA / PAAm was drop-coated and polymerized as a sample. A halogen lamp included with an optical microscope (Keyence, VHX-1000) was used as a light source, and the transmitted light from the sample fixed to the temperature console was detected with a spectrophotometer (Hamamatsuphotonics, PMA-12) to provide a UV-Vis spectrum.

[0148] (6) Fourier transform infrared spectroscopy (FT-IR) In order to observe the interaction between PCDA and each guest polymer and to observe the change of the interaction before and after the color change, infrared absorption spectra were obtained with a Fourier transform infrared spectrophotometer (Jasco, FT / IR-4200, Shimadzu, AIM-8800) by using the KBr method and the ATR method.

[0149] (7) Differential Scanning Calorimeter (DSC) In order to analyze the thermal behavior of the PDA / alkyl-based polymer guest, measurement was performed using a differential scanning calorimeter (Shimadzu Science East Corporation, DSC-60 Plus).

[0150] (8) Raman spectrometer In order to compare the polymerization rate of PCDA / polymer guest, measurement was performed using a Raman spectrometer (Renishaw, InVia Raman Microscope). The measurement was performed by bonding a carbon tape to the upper lid of a styrene square box and fixing the powder of the sample to the tape.

[0151] (9) Image analysis (chromaticity diagram) The color change of PDA / polymer object was quantitatively analyzed by image analysis. The RGB value analysis of the photograph of the composite was performed with image analysis software (ImageJ). The results were converted to the CIE 1931 color system based on the determined RGB values. The equation for conversion is shown below.

[0152]

[0153] 3. Results (1) Preparation and evaluation of PCDA / alkyl and pyridine polymer guests PCDA / polymer guests were prepared by a direct synthesis method using PEI, PVAm and PAAm as alkyl-based polymers and PVP4 and PVP2 as pyridine-based polymers. The prepared composites before polymerization were evaluated based on the analysis of XRD patterns and IR spectra.

[0154] exist Figure 3 (A) shows XRD patterns of PCDA crystals and PCDA / PEI, PCDA / PVAm, and PCDA / PAAm, which are used as PCDA / alkyl polymer guests, respectively. In PCDA crystals, peaks can be observed at 2θ / θ=1.85°, 3.65°, 7.37°, and 13.0°, and the peaks can be attributed to d0=4.68 nm. After the formation of the composite with the guest polymer, peaks can be observed at 2θ / θ=1.71°, 2.48°, and 5.04° in PCDA / PEI, at 2θ / θ=1.67°, 5.10°, and 8.27° in PCDA / PVAm, and at 2θ / θ=1.28° in PCDA / PAAm, and the peaks can be attributed to d0=5.51 nm, 5.63 nm, and 7.05 nm, respectively. Therefore, it was found that the guest polymer was introduced between the PCDA layers because a shift of the peak indicating the interlayer distance was observed when a composite with the guest polymer was formed.

[0155] exist Figure 3 (B) shows the IR spectra of PCDA crystals and PCDA / alkyl polymer guest. In the precursor PCDA crystal, the IR -1 An absorption peak (A) originating from the C=O stretching vibration of the carboxyl group (-COOH) forming the dimer through hydrogen bonding was observed near 1,700 cm -1 The absorption peak near 1,550 cm -1 Up to 1,650 cm -1An absorption peak (B) was observed at 1.30°, which originated from the carboxylate anion (-COO - ) stretching vibration. Based on the above, it was found that in the precursor PCDA crystal, the carboxyl group (-COOH) at the end formed a dimer; however, it became a carboxylate anion (-COO - ).

[0156] exist Figure 4 (A) shows the XRD patterns of PCDA crystals and pyridine-based polymer guests. In PCDA crystals, peaks can be observed at 2θ / θ=1.85°, 3.65°, 7.37°, and 13.0°, and the peaks can be attributed to d0=4.68 nm. After the composite with the guest polymer is formed, peaks can be observed at 2θ / θ=1.77° and 5.74° in PCDA / PVP4, and at 2θ / θ=1.64° in PCDA / PVP2, and the peaks can be attributed to d0=4.88 nm and 5.44 nm, respectively. Therefore, it was found that the guest polymer was introduced between the PCDA layers because a shift in the peak indicating the interlayer distance was observed when the composite with the guest polymer was formed.

[0157] exist Figure 4 (B) shows the IR spectra of PCDA crystals and PCDA / pyridine polymer guests. In the precursor PCDA crystal, the IR -1 An absorption peak (A) was observed near 1,700 cm-1, which is derived from the C=O stretching vibration of the carboxyl group (-COOH) formed by hydrogen bonding to form a dimer. -1 The absorption peak near 1,600 cm was shifted to the low wave number side. From the above findings, the PCDA molecule, which is a precursor of the dimer formed by hydrogen bonding of carboxylic acid, was monomerized in the PCDA / pyridine polymer guest. In addition, the stretching vibration of the pyridine ring at 1,600 cm -1 The absorption peak near (B) shows that the absorption peak of PCDA / pyridine polymer guest is shifted to the high wave number side compared with the absorption peak of pyridine polymer guest. This indicates that the hydrogen bond becomes stronger. From the results mentioned above, it is found that the monomerized precursor PCDA and the pyridine polymer guest interact with each other through hydrogen bonds.

[0158] When the XRD pattern and IR spectrum were measured by setting the composition ratio "PCDA: pyridine polymer guest" to 1:3, 1:4, 1:5, and 1:10 in addition to 1:2 to produce a sample (data not shown), PCDA and the pyridine polymer guest formed a complex at all the composition ratios. Therefore, it is inferred that when the ratio "PCDA: pyridine polymer guest" is 1:2 or more, the amount of the interlayer guest does not change. Hereinafter, only the sample with a ratio "PCDA: pyridine polymer guest" of 1:2 was evaluated.

[0159] (2) Changes in PCDA / alkyl and pyridine polymer guest complexes after UV irradiation exist Figure 5 , a photograph of PDA / polymer guest obtained by irradiating PCDA / each of five polymer guests with UV light to perform topochemical polymerization is shown in FIG. Figure 5 (E) and Figure 5 In each of (F), the color change was insufficient. From the foregoing, it is conceivable that polymerization did not proceed sufficiently in PDA / PVP4 and PDA / PVP2.

[0160] exist Figure 6 FIG. 5 shows changes in the peak intensity ratio of each composite with respect to UV irradiation time, that is, the polymerization rate (the peak intensity is based on the peak of the Raman spectrum measured with a Raman spectrometer).

[0161] Peak intensity ratio = Peak intensity of carbon-carbon triple bond derived from ene-yne ​​skeleton / Peak intensity of carbon-carbon triple bond derived from monomer like Figure 6 As shown in , PCDA has the fastest polymerization rate, the alkyl polymer guest complexes each have the second fastest polymerization rate, and PCDA / PVP4 and PCDA / PVP2 used as pyridine polymer guest complexes each have the slowest polymerization rate. In order to polymerize, PCDA molecules are required to be aligned at an angle and intermolecular distance that allow polymerization because PCDA has the property of undergoing topochemical polymerization. However, the pyridine polymer guest is very large and thus greatly increases the flexibility of the complex. Therefore, the alignment characteristics required for polymerization cannot be maintained, and the polymerization rate slows down. From the foregoing, it is conceivable that polymerization is not fully performed.

[0162] Therefore, evaluation of the temperature-responsive color change of only PDA / PEI, PDA / PVAm, and PDA / PAAm, which serve as composites of alkyl guests in which polymerization proceeds sufficiently, is performed hereinafter.

[0163] (3) Temperature responsiveness of PDA / alkyl polymer guests Each of the PDA, PDA / PEI, PDA / PVAm, and PDA / PAAm polymers was gradually heated from a low temperature, and the color changes at the corresponding temperatures were photographed. The color change photographs are shown in Figure 7 middle.

[0164] From Figure 7 The color change temperature range indicated by the arrow in the figure shows that the color change onset temperature of PDA / alkyl polymer guest is lower and the color change temperature width is increased compared with those of PDA. Figure 7 First, the color changes of the corresponding samples at the corresponding temperatures are plotted on the chromaticity diagram ( Figure 8 Next, calculate the distance between the measurement start point of the corresponding sample and the corresponding drawing. Figure 8 (B) shows the relationship between the distance between the measurement start point and the corresponding plot with respect to temperature increase.

[0165] based on Figure 8 The (B) determined color change temperature range is shown in Table 1.

[0166] From Table 1, it is found that the color change start temperature of the PDA / alkyl polymer guest is lowered and the color change temperature width thereof is increased compared to those of PDA. In addition, as the volume of the guest polymer increases, the color change temperature of the PDA / alkyl polymer guest is lowered more and the color change temperature width thereof is increased more. Regarding PDA / PAAm showing the maximum temperature decrease and the maximum width increase, further temperature responsiveness evaluation was performed by UV-vis measurement. Fig. 9 (A) and Fig. 9 The results of UV-vis measurements are shown in (B). PDA and PDA / PAAm were each heated from -50°C to 220°C and measured at the corresponding temperatures. The absorption peak of PDA shifts sharply to the low wavelength side near 60°C. At the same time, in response to the temperature change, the absorption peak of PDA / PAAm gradually shifts from low temperature to the low wavelength side. Therefore, it was also found from the results of UV-vis measurements that PDA / PAAm exhibits a specific color change caused by the introduction of the guest polymer.

[0167] Table 1. Color change temperature range of PDA and PDA / alkyl polymer guests

[0168] The color change is caused by the twisting of the PDA backbone. Therefore, from the graph showing the twisting angle of the PDA backbone relative to the wavelength of maximum absorption, the ease of perturbation of the PDA layer, that is, the flexibility of the composite, can be estimated based on the color change. Fig. 9 (A) and Fig. 9 (B) UV-vis spectra and graphs of each ( Fig.10 (A) and Fig.10 (B) Determination of the torsion angles of the conjugated chains of PDA and PDA / PAAm at corresponding temperatures.

[0169] like Fig.10 As shown in (A), the conjugated chains of PDA are twisted sharply at 60°C to 70°C. Fig.10 As shown in (B), the conjugated chains of PDA / PAAm gradually twist as the temperature increases. The twist angles of the conjugated chains corresponding to the color changes of PDA and PDA / PAAm were observed. For PDA, the twist angle ranged from 3° to 35°, and for PDA / PAAm, the twist angle ranged from 15° to 47°. When the maximum values ​​of the twist angles are compared with each other, it is conceivable that PDA / PAAm has a higher layer structure flexibility than PDA.

[0170] exist Fig.11 The measurement results of PDA / alkyl-based polymer guests with DSC are shown in FIG. Fig.11 The arrow in indicates the starting temperature of the endothermic peak. As the volume of the guest polymer becomes larger, the starting temperature of the endothermic peak decreases. The endothermic peak of DSC appears due to the molecular motion of the complex (i.e., the perturbation of the layer structure). The color change of the complex is caused by the torsion of the PDA main chain caused by the perturbation of the layer structure. From the above, it is thought that: because the flexibility of the complex increases as the volume of the guest polymer becomes larger and thus the perturbation of the layer structure is easily caused by a small thermal stimulus (i.e., from a low temperature), a reduction in the color change temperature is achieved; and because the layer structure is gradually disturbed, the color change temperature width increases.

[0171] (4) Comparison of preparation methods of PCDA / alkyl polymer guest complexes In the previous section, samples of PCDA / alkyl polymer guest complexes were prepared by a direct synthesis method. However, in this section, samples were prepared by a layer-by-layer method (LbL method) in anticipation of lamination by stronger electrostatic interactions. Preparation was performed by the LbL method. Polymerization of the PCDA / alkyl polymer guest complex was performed by irradiation with UV light (254 nm).

[0172] The prepared composite before polymerization was evaluated by analyzing the XRD spectrum. As a result, in the PCDA crystal, peaks can be observed at 2θ / θ=1.85°, 3.65°, 7.37°, and 13.0°, and the peaks can be attributed to d0=4.68nm. After the introduction of the guest polymer, in PCDA / PEI, peaks can be observed at 2θ / θ=1.73°, 2.12°, 5.10°, and 5.25°, in PCDA / PVAm, peaks can be observed at 2θ / θ=1.71°, 5.06°, and 5.53°, and in PCDA / PAAm, peaks can be observed at 2θ / θ=1.48° and 5.62°, and the peaks are attributed to d0=5.08 nm, 5.26 nm, and 6.40 nm, respectively (curve graph omitted). Therefore, it was found that the guest polymer was introduced between the PCDA layers because a shift of the peak indicating the interlayer distance was observed when a composite with the guest polymer was formed.

[0173] In addition, according to the analysis of IR spectra, no C=O stretching vibration at 1,700 cm-1 originating from the carboxyl group (-COOH) forming the dimer was observed in the PCDA / alkyl polymer guest complex. -1 The absorption peak near (A) and at 1,550 cm -1 Up to 1,650 cm -1 The carboxylate anion (-COO - ) of the C=O stretching vibration (B) (graph omitted). Based on the above, it was found that the carboxyl group (-COOH) at the end of the main layer PCDA formed a complex with the amine of the guest polymer to become a carboxylate anion (-COO - ).

[0174] Therefore, it is recognized that PCDA and the alkyl-based polymer guest form a complex in the sample prepared by the LbL method as well as in the sample prepared by the direct synthesis method.

[0175] Furthermore, in the color photographs obtained when the corresponding polymer samples are gradually heated from a low temperature and the color changes at the corresponding temperatures are photographed, as shown in FIG. Figure 7 Compared to the color change behavior of the samples prepared by the direct synthesis method shown in , no significant differences were found (data not shown). Even when the samples were prepared by the LbL method, a decrease in the color change temperature and an increase in its width could be observed in the same manner as in the direct synthesis method.

[0176] Using an optical microscope ( Fig.12 (A) to Fig.12 (C)) and SEM ( Fig.13 (A) to Fig.13(C) Observation of the structure of the corresponding composite prepared and polymerized by the LbL method. In PDA / PEI, the amount of the sample formed on the substrate is small, and in each of PDA / PVAm and PDA / PAAm, the sample formed on the substrate is non-uniform. Possible factors of such non-uniformity are, for example, as follows: in the process of alternately laminating the host solution and the guest solution, aggregation of the host molecules and aggregation of the guest molecules occur randomly on the substrate, and thus the thickness of each layer becomes non-uniform.

[0177] (5) Observation of PDA / PAAm coatings by various coating methods Silk cloth was coated with the PDA / PAAm composite by various coating methods, and the state of the coating was observed with a typical camera and optical microscope.

[0178] Fig.14 (A) and Fig.14 (D) is a photograph of a silk cloth coated with a PDA / PAAm composite by a dip coating method taken with a camera and an optical micrograph thereof. The solution conditions were set to be the same as those in 1. (1) of Test 1. The silk cloth was immersed in the PDA / PAAm solution, and the silk cloth was lifted up and dried.

[0179] Fig.14 (B) and Fig.14 (E) is a photograph of the silk cloth coated with the PDA / PAAm composite by the volatilization method taken with a camera and an optical micrograph thereof. The solution conditions were set to be the same as those in 1. (1) of Test 1. The solution was evaporated while the silk cloth was immersed in the PDA / PAAm solution.

[0180] Fig.14 (C) and Fig.14 (F) is a photograph of a silk cloth coated with a PDA / PAAm complex by a spraying method taken with a camera and an optical micrograph thereof. A solution of the PCDA / PAAm complex was applied to the silk cloth by spraying from a position 20 cm away from the silk cloth. The silk was placed in a constant temperature bath at 4°C so that the solvent was volatilized and removed. The PCDA / PAAm complex of the obtained silk cloth was solid-state photopolymerized by irradiation with UV light. A UV-LED lamp (CCS Inc., HLDL-120X30UV265-PSC, 265 nm) or a hand lamp (AS ONE, Handy UV Lamp SLUV-6, 254 nm) was used as a light source.

[0181] In the case of each of the dip coating method and the volatilization method, the color of the silk cloth was light, and the PDA / PAAm composite was not uniformly attached to the silk cloth. Fig.14 (C) and Fig.14 In the case of (F), the PDA / PAAm composite is uniformly attached to the silk fabric.

[0182] Test 2 Increase in the area of ​​PDA / PAAm composites, measurement of their specific heat, and their application in medical surgery Research examples of increasing the area of ​​polydiacetylene devices by film device formation and inkjet printing have been reported. Most of the research examples of area increase are examples of inkjet printing on independent films or papers, and research in the field of uniform coating on various substrates on a centimeter scale is still underdeveloped. When such coating is achieved, the application can be expanded to a variety of applications, such as temperature imaging in various situations.

[0183] In this example, large area substrates of PDA / alkyl polymer guest were fabricated, followed by coating performance comparisons on a centimeter scale. By utilizing the color change characteristics and coating performance of PDA / PAAm, an attempt was made to estimate the value equivalent to specific heat with a bondable seal substrate, and real-time temperature imaging was performed with a silk cloth substrate.

[0184] 1. Experimental Methods (1) Applying PCDA / polymer guest to polymethyl methacrylate (PMMA) substrate by spray coating 80 mg of PCDA was dissolved in 8 ml of ethanol or 16 ml of hexane to produce a PCDA solution. The solution was filtered with a funnel and filter paper to remove the polymer of PCDA. 0.5 ml of ethanol and 20.2 mg of PEI or 119.7 μl of PAAm were added to the filtered PCDA ethanol solution, and 1 ml of hexane and 5.74 mg of PVAm were added to the filtered PCDA hexane solution. The PCDA / alkyl polymer guest mixed solution was dispersed with ultrasound for 30 minutes, and then the solution was applied to an 18 cm×18 cm PMMA substrate in an upright state from its bottom in sequence from a position 20 cm away from the substrate by spraying. The substrate was placed in a constant temperature bath at 4°C so that the solvent was volatilized and removed. Thus, a PMMA substrate device of PCDA / alkyl polymer guest was obtained. The obtained PCDA / alkyl polymer guest complex was solid-state photopolymerized by irradiation with UV light. Use a UV-LED lamp (CCS Inc., HLDL-120 X30UV265-PSC, 265 nm) or a hand lamp (ASONE, Handy UV Lamp SLUV-6, 254 nm) as the light source.

[0185] (2) PDA / PAAm drop coating on bondable seals 50 mg of PCDA was dissolved in 5 ml of ethanol to prepare a PCDA solution. The solution was filtered with a funnel and filter paper to remove the polymer of PCDA. 74.8 ml of PAAm was added to the filtered PCDA ethanol solution and dispersed with ultrasound for 30 minutes. The solution was drop-coated on a 3.5 cm×7.5 cm bondable seal (a seal comprising a transparent sheet made of polyvinyl chloride, the transparent sheet having an adhesive on one surface of the sheet, the sheet being used by peeling off the release paper on the adhesive and bonding it to an object), which was fixed to a smooth plate with masking tape. The seal was placed in a constant temperature bath at 4°C so that the solvent was volatilized and removed. Thus, a bondable seal device of PCDA / PAAm was obtained. The obtained PCDA / PAAm composite was subjected to solid-state photopolymerization by irradiation with UV light. Use a UV-LED lamp (CCSInc., HLDL-120X30UV265-PSC, 265 nm) or a hand lamp (AS ONE, Handy UV Lamp SLUV-6, 254 nm) as the light source.

[0186] (3) Applying PDA / PAAm to silk fabric by spraying 40 mg of PCDA was dissolved in 12 ml of ethanol to prepare a PCDA solution. The solution was filtered with a funnel and filter paper to remove the polymer of PCDA. 59.8 ml of PAAm was added to the filtered PCDA ethanol solution and dispersed with ultrasound for 30 minutes. Four 3 cm×3 cm silk cloths were each fixed to a smooth plate with masking tape, and half the amount of the solution was applied to the plate by spraying from 20 cm above the plate. The plate was placed in a constant temperature bath at 4°C to volatilize the solvent. The next day, the remaining solution was applied to the plate by spraying. The plate was placed in a constant temperature bath at 4°C to volatilize the solvent. Thus, a silk cloth device of PCDA / PAAm was obtained. The obtained PCDA / PAAm complex was solid-state photopolymerized by irradiation with UV light. Use a UV-LED lamp (CCS Inc., HLDL-120X30UV265-PSC, 265 nm) or a hand lamp (ASONE, Handy UV Lamp SLUV-6, 254 nm).

[0187] (4) Observation of the color change behavior of silk fabric coated with PDA / PAAm in response to heat The color change behavior of the silk cloth coated with PDA / PAAm to heat was observed. The glass substrate on which the sample was drop-coated or the paper substrate coated with the sample was placed on a temperature stage, and heating was performed from 30° C. to 120° C. The sample was kept at each temperature for 2 minutes and then photographed.

[0188] 2. Evaluation Methodology (1) Scanning electron microscopy (SEM) The glass substrate on which the PDA / polymer guest was drop-coated was fixed to an aluminum stage with a conductive tape. Osmium coating was performed to ensure conductivity. Thereafter, the detailed structure of the sample was observed with a scanning electron microscope (S-2700; Hitachi, Sirion; FEI, JSM-7600F; Jeol).

[0189] (2) Image analysis (vertical axis x) The color change of PDA / APDES caused by friction was quantitatively analyzed by image analysis. R, G and B values ​​were calculated from the photos using software (ImageJ). The results were converted to the XYZ color system using the Rec.709 standard. The equation for conversion is shown below.

[0190]

[0191] 3. Results exist Fig.15 (A) to Fig.15 (D) shows a photograph of an ethanolic PDA solution and an ethanolic precursor solution of PCDA / polymer guest each applied to a polymethyl methacrylate (PMMA) substrate by spray coating and polymerized by UV irradiation. The macroscopic uniformity of the coating increases as the volume of the guest polymer increases.

[0192] exist Fig.16 (A) to Fig.16 (D) shows Fig.15 (A) to Fig.15(D) SEM image of the corresponding substrate. In addition, on a microscopic scale, as the volume of the guest polymer increases, the uniformity of the coating increases. The forms of the corresponding composites were observed from the SEM images. The form of PDA was a plate-like crystal with a thickness of 0.20 ± 0.025 μm and a size of 17.52 ± 6.25 μm × 12.25 ± 4.26 μm, the form of PDA / PEI was an amorphous shape with a thickness of 0.34 μm and a size of 29.81 ± 8.99 μm × 9.00 ± 2.81 μm, the form of PDA / PVAm was a ribbon shape with a width of 0.22 ± 0.14 μm and a length of 5.54 ± 2.43 μm, and the form of PDA / PAAm was a spherical shape with a particle diameter of 2.07 ± 1.04 μm. As the volume of the guest polymer increases, the size of the composite decreases. The possible factors are as follows: as the guest polymer becomes more bulky, the crystals of the guest molecules are hardly formed, and there are a large number of guests around the PDA crystals, and thus the crystal growth of PDA is suppressed. In PDA / PAAm using the most bulky guest polymer, the most uniform coating with a large area is achieved.

[0193] 4. Use PDA / PAAm to estimate the value equivalent to specific heat Attempt to estimate the value equivalent to specific heat by using the adhesive seal coated with PDA / PAAm. The adhesive seal coated with PCDA / PAAm is bonded to the side surface of the container made of stainless steel, and 100 g of the liquid used as the measurement object is loaded into the container. In order to prevent the mass change caused by evaporation of the liquid, the container is covered with plastic packaging and sealed with masking tape. The container is allowed to stand on a hot stage of 70°C to be heated, and a video of its appearance is taken. During heating, the container is closed, and the upper part of the hot stage is covered with a foam box so as not to be affected by temperature changes such as ambient environment. A hole is made on the foam box for taking a video, and the hole is sealed with a transparent polymethyl methacrylate plate. The interior of the box darkens, and therefore the seal coated with PDA / PAAm on the side surface of the container is illuminated from the outside of the box with an LED desk lamp, so that the video of the color change of PDA / PAAm is accurately taken.

[0194] Videos were taken for each of the cases where 100 g of silicone oil, ethanol, and water were loaded into a container as solutions used as measurement objects by the above method. In order to perform image analysis on the taken videos, the videos were played on a personal computer, and the videos were paused at the corresponding heating time to take screenshots, and the images of only the PDA / PAAm portion were cut out using the trimming function of PowerPoint. As a result of the image analysis, the heating time before the stable state of the color change of the seal was compared with each other in the curve graph, and it was found that the color change corresponding to the literature value of the specific heat was shown.

[0195] The definition formula of specific heat c is as described below.

[0196]

[0197] In this formula, it is considered that the thermal energy difference ΔQ of the object corresponds to the total time t of heating the hot stage at a constant temperature of 70° C. from the start of heating the hot stage until the color change becomes stable. 总 In addition, it is contemplated that a temperature change ΔT corresponds to Δx0→max from the following equation.

[0198]

[0199] Therefore, the specific heat equivalent value c' is expressed by the following equation.

[0200]

[0201] exist Fig.17 The relationship between the specific heat equivalent value of each solution used as the measurement object and the value of the liquid having the same specific heat of the literature is shown in the heating time before the steady state of the color change is measured from the slope of the approximate straight line of the graph. The calibration curve that allows the specific heat to be estimated from the specific heat equivalent value is determined as the following equation. c represents the specific heat, and c' represents the specific heat equivalent value.

[0202]

[0203] The specific heat of an unknown solution can be estimated by using this equation as a calibration curve. For example, when a container filled with 100 g of a 50 wt% ethanol aqueous solution is heated, a color change image of the PDA / PAAm seal on the side surface of the container is taken, and the relationship between the calculated specific heat equivalent value and the specific heat of the literature value is determined. As a result, the relationship corresponds to the calibration curve ( Fig.17 point (d)).

[0204] 5. Temperature imaging in medical surgery using PDA / PAAm An attempt was made to perform real-time temperature imaging to prevent burns caused by electric scalpels in medical surgery. A temperature imaging sheet obtained by applying a PCDA / PAAm mixed solution to a silk cloth by spraying was used.

[0205] The temperature at which burns occur (i.e., the temperature at which protein denaturation occurs) is about 60°C, and is within the color change temperature region of the sheet containing the PDA / PAAm polymer complex. Therefore, while noting the color change of the temperature imaging sheet, sites within the temperature range of 60°C or higher can be detected.

[0206] Assume that during surgery a temperature imaging patch is attached to the organ, e.g. Fig.18 As shown in , a temperature imaging sheet is attached to a piece of pork, and the piece of pork is heat-treated with an electric scalpel. Thus, the color change around the treated part is analyzed using an image.

[0207] Fig.19 (A) is a photograph of a piece of meat being cut using ultrasonic waves on the outer side (the curved side of the blade) of an electric scalpel A (ultrasonic coagulation cutting device that performs cutting by ultrasonic vibration). Fig.19 (B) is a photograph of a piece of meat being cut using electric power on the outer side of an electric scalpel B (including a blood vessel sealing system for cutting using Joule heat). Fig.19 (C) is a graph showing the relationship between the distance z (horizontal axis) from the cutting site of the piece of meat and the red intensity (x, left axis) and estimated temperature (right axis) of the piece when the electric scalpel A and the electric scalpel B are used. Fig.19 (D) is a calibration curve showing the relationship between the red intensity of the patch (x, left axis) and the actual measured temperature of the patch (right axis).

[0208] like Fig.19 (A) and Fig.19 As shown in each of (B), the distance z from the cut site on the piece of meat is the distance from the edge of the cut piece of meat to the measuring site on the piece of meat in the direction away from the cut site. The red intensity x of the piece is calculated by image analysis using an image captured from a photograph of the piece. R, G and B values ​​are calculated from the image of the piece using software (ImageJ), and the R, G and B values ​​are converted to an XYZ color system by using the Rec.709 standard. The equations for conversion are shown below.

[0209]

[0210] According to the red intensity x of the sheet and Fig.19(D) The estimated temperature T of the piece was calculated using the calibration curve. In the case of using electric scalpel A, when the piece was cut three times, the average value of the distance z from the cut portion of the piece of meat indicated as 60°C or higher by analyzing the color of the temperature imaging piece was 1.32±0.405 mm. In the case of using electric scalpel B, when the piece was cut three times, the average value of the distance z was 2.34±0.698 mm. It should be understood that when using electric scalpel B, the portion of 60°C or higher is distributed in a wide range starting from the cut portion, and therefore the heat-affected range is wider than that of electric scalpel A. At the same time, when using ultrasonic waves with electric scalpel A, the highest achievable temperature of the temperature imaging piece is higher than when using ultrasonic waves with electric scalpel B. Even when the piece was cut with the inner side of electric scalpel A, the same result was obtained (data omitted).

[0211] Test 3 Preparation and evaluation of complexes of PCDA, PAAm and low molecular weight amines (1) Preparation of PCDA / guest complex 30 mg of PCDA was dissolved in 20 ml of solvent to prepare a PCDA solution. The solution was filtered using a funnel and filter paper to remove the polymer of PCDA. Four low molecular weight amines used as guests (all p-xylylenediamine, 1,4-bis(aminomethyl)cyclohexane (c-C6-(CH2NH2)2 (mixture of cis and trans isomers)), 1,12-dodecanediamine (C 12 -(NH2)2) and stearylamine (C 18 -(NH2))) was added to the filtered solution so that the ratio between the amount of the cationic part of each guest and the amount of the carboxyl group of PCDA became 1:1. After performing ultrasonic stirring for 30 minutes, the solvent was removed from the prepared precursor solution by solvent volatilization. Thus, a PCDA / guest complex was obtained. The obtained PCDA / guest complex was solid-state photopolymerized by irradiation with UV light. A UV-LED lamp (CCS Inc., HLDL-120X30UV265-PSC, 265 nm) or a hand lamp (AS ONE, Handy UV Lamp SLUV-6, 254 nm) was used as a light source.

[0212]

[0213] (2) Preparation of PAAm / PDA-guest phase separation structure (2-1) Investigation of changes in the amount of PAAm introduced and the reversibility of color change 30 mg of PCDA was dissolved in 20 ml of solvent to prepare a PCDA solution. The solution was filtered with a funnel and filter paper to remove the polymer of PCDA. Each of the guest molecules as low molecular weight amines was added to the filtered solution so that the ratio between the amount of the cationic part of each of the four low molecular weight amines mentioned above and the amount of the carboxyl part of PCDA became 1:1. After performing ultrasonic stirring for 30 minutes, any amount of PAAm was added, and the product was further ultrasonically stirred for 60 minutes. The solvent was removed from the prepared precursor solution by solvent volatilization, and the product was UV irradiated. Therefore, a PAAm / PDA / guest phase separation structure was obtained.

[0214] Unless otherwise specified, various evaluation methods below were performed in the same manner as in Test 1.

[0215] When the structure of polyallylamine having a unit represented by the general formula (1) is set as one unit, the introduced amount of PAAm is defined as the molar ratio relative to PCDA in the sample, and the introduced amount of p-xylylenediamine (hereinafter referred to as "p-Xy") is defined as the molar ratio of PCDA.

[0216] p-Xy was set to 0.5, and the color change when the temperature was increased from 25°C to 118°C and the reversibility when cooled to 20°C were evaluated when the amount of PAAm introduced was changed in the range of 0 to 2 (0, 0.5, 1, 1.33, 1.66, 2). There was no color reversibility in PDA-PAAm. Fig. 20 As shown in (A), the color change at elevated temperature does not depend to a large extent on the amount of PAAm introduced. Fig. 20 (A) and Fig. 20 As understood from the comparison between (B), when the amount of PAAm is large, there is a tendency for the reversibility to be poor. It was found that the case where the amount of PAAm introduced is 1.33 or less is more preferable from the viewpoint of reversibility.

[0217] (2-2) Investigation of the Change in the Quantity of p-Xy and the Reversibility of the Color Change Next, the color change when the temperature was increased from 25°C to 118°C and the reversibility when cooled to 20°C were evaluated while fixing the ratio between PDA and PAAm at a molar ratio of 1:1 and varying the amount of p-Xy in the range of 0.2 to 0.5 (molar ratio relative to PCDA). Fig.21In the graph, the solid lines indicate the color change of the complex containing three amounts of p-Xy when the temperature is increased, and the dotted lines indicate the color change of the complex containing three amounts of p-Xy when cooling. The larger arrow on the right side of the graph indicates that the reversibility of the color change is greater. In this experiment, when p-Xy is 0.5, the maximum reversibility is shown.

[0218] (2-3) Investigation of the introduction distribution of p-Xy and PAAm Subsequently, experiments were performed to change the introduction distribution of p-Xy and PAAm. When the number of carboxyl groups of PCDA was set to 1, the number of amino groups present was fixed to 1, and five PAAm / PDA-p-Xy were prepared at the mixing ratios shown in Table 2. The IR measurement results of the corresponding samples are shown in Fig. 22 In. According to Fig. 22 , PAAm / PDA-p-Xy and PDA-p-Xy showed similar peaks regardless of the amount of p-Xy and PAAm. In addition, images of the composites of samples II, III and IV were taken under an optical microscope, and the images were obtained by performing RGB image analysis on the images. Fig.23 (A) to Fig.23 (C) It was found that even when the amount of p-Xy was 0.125 (which is extremely small), the domain showing reversibility occupied a large part. From these results, it was found that when the amount of p-Xy introduced was less than 0.5 and the carboxyl group of PCDA could not completely meet the amino group of p-Xy, PDA-p-Xy was also formed, and the formation of a complex between p-Xy and PCDA was more dominant than that between PAAm and PCDA.

[0219] Table 2 Introduced ratios of corresponding molecules of samples I to V in the experiment of changing the introduced distribution of p-Xy and PAAm

[0220] (2-4) Observation of the complex using an electron microscope Next, in Fig.24 (A) to Fig.24(D) shows secondary electron images of PDA-p-Xy and PAAm / PDA-p-Xy. The samples were prepared by applying each of the precursor solutions of PCDA-p-Xy and PAAm / PCDA-p-Xy to a silicon substrate by spraying and volatilizing the solution. PDA-p-Xy is in a state where rectangular thin plate-like crystals each measuring about 1 μm long and about 5 μm wide are stacked, and PAAm / PDA-p-Xy is in a state where rectangular thin plate-like crystals each measuring about 0.5 μm long and about 2 μm wide are aggregated. According to the backscattered electron image, in PAAm / PDA-p-Xy, a white portion ( Fig.24 In the backscattered electron image, white indicates an amorphous portion, and further, white is not observed in PDA-p-Xy ( Fig.24 (C)). Therefore, it is thought that the white portion around the plate-like crystals in PAAm / PDA-p-Xy indicates the location of PAAm.

[0221] From the results mentioned above, it is thought that PAAm / PDA-p-Xy forms a "phase separation structure" ( Fig.25 ).

[0222] (3) Preparation of composites using various low molecular weight amines (3-1) Preparation of composites using various low molecular weight amines PAAm / PDA-guests were prepared by using other low molecular weight amines instead of p-Xy as guests and evaluated. The low molecular weight amines used as guests in this case are shown below.

[0223]

[0224] Each of PAAm / PCDA-guest and PCDA-guest was prepared by using the ethanol solvent as in (1) of Test 3, and the IR measurement results and XRD measurement results thereof are shown in Fig.26 (A) and Fig.26 (B) in.

[0225] according to Fig.26In the IR measurement results of (A), in any sample, the peak due to the carboxylic acid dimer disappeared and the peak due to the carboxylate ion appeared. Therefore, it was found that the guest was embedded between the PCDA layers. The peak of the PCDA-guest and the peak of the PAAm / PCDA-guest were compared with each other, and the same degree of peaks appeared at the same wavelength in all four guests. Therefore, it was found that in the PCDA-guest and the PAAm / PCDA-guest, the functional groups between the layers were in substantially the same state. Fig.26 In the XRD measurement results of (B), an increase in the interlayer spacing d0 appears in each sample. In addition, when the interlayer spacing d0 of PCDA-guest and the interlayer spacing d0 of PAAm / PCDA-guest are compared with each other, the interlayer spacing d0 becomes values ​​extremely close to each other. From these measurement results, it is found that molecules are newly introduced between the layers of PCDA in each of PAAm / PCDA-guest and PCDA-guest, and regardless of the presence or absence of PAAm, the change in the state of the functional group and the increase in the width of the interlayer spacing correspond to each other with the introduction of the molecules.

[0226] (3-2) Temperature-responsive color change behavior of the composite Subsequently, the color change behavior when the temperature of each of the PAAm / PDA-guests was controlled was observed with an optical microscope. The corresponding samples were each prepared by applying the solution to a glass slide by spraying, and the observation was performed by superimposing a clean paper on the rear surface of the glass. In addition, Fig. 27 The color change behaviors of PAAm / PDA-guest and PDA-guest on a centimeter scale are shown in FIG.

[0227] The red color change of PAAm / PDA-c-C6-(CH2NH2)2 from 80°C to 100°C and the reversibility up to about 100°C are consistent with those of PDA-c-C6-(CH2NH2)2. 12 -(NH2)2 showed different color change behaviors at two sites (not shown). In one region, reversibility from red to blue was observed by the change from 100°C to 25°C, and it is thought that this behavior is based on PDA-C which showed a color change at 120°C and was reversible. 12 -(NH2)2 domains. In another region, color change and irreversibility were observed up to 100 °C. This behavior is similar to that of PDA-PAAm domains. 12 -(NH2)2, there is a high probability that these two domains are produced separately. Fig. 27 It was found that in PAAm / PDA-C 12-(NH2)2, the two domains are mixed. 18 -NH2, the color change was complete by 80°C, and no reversibility was observed. This behavior roughly corresponds to that of PDA-C 18 -NH2 shows a transition color change at 85°C. Fig. 27 It can be seen that PDA-PAAm is mixed.

[0228] According to the results mentioned above, when c-C6-(CH2NH2)2 and C 18 When -NH2 was used as the guest, PCDA-guest was preferentially formed as a complex. It is contemplated that in each of the PAAm / PDA-guests using those complexes, a Fig.25 At the same time, it was found that when PDA-C 12 -(NH2)2 is used as the guest, both PDA-guest and PDA-PAAm are formed. Therefore, in order to prepare an ideal single PDA domain for forming a PAAm / PDA-guest phase separation structure showing a temperature-responsive color change behavior of a PDA-guest, it is preferred to select a guest that easily causes complex formation and aggregation of a PDA-guest, represented by p-Xy.

[0229] (4) Optimization of coating method (4-1) Selection of coating method The amount of PCDA was set to 1, the amount of p-Xy was set to 0.5 (molar ratio), and the amount of PAAm was set to 0 mol and 1.3 mol, and spray coating, dip coating, and drop coating were investigated as coating methods.

[0230] In spray coating, 10 mL of PAAm / PCDA-p-Xy precursor solution was sprayed from a spray container onto a 2 cm×2 cm substrate at 45° from above. The number of sprays was set to one. In dip coating, the substrate was immersed in 20 mL of PAAm / PCDA-p-Xy precursor solution prepared in a beaker for 10 seconds and then lifted up. In drop coating, the substrate was allowed to stand in 10 mL of PAAm / PCDA-p-Xy precursor solution prepared in a petri dish, and then the substrate was allowed to stand as it was for about a day and a half to allow the solvent to be volatilized. Silk cloth substrates and filter paper substrates were used as substrates.

[0231] In each of the substrates, when viewed on a centimeter scale, the coating becomes most uniform in spray coating. Drop coating requires a long period of time for solvent volatilization, and therefore it is conceivable that during this period of time, crystals aggregate at various points by intermolecular forces, resulting in an uneven state. Dip coating is not suitable as a coating method because the amount of solution that can be attached to the substrate is small. It is conceivable that spray coating is suitable for uniform coating from the perspective that fine droplets are uniformly released into the space and a certain amount of solvent is volatilized when spraying.

[0232] Furthermore, also in the spray coating where the most uniform coating characteristics were observed, non-uniformity was observed when the amount of PAAm was 0 mol. Therefore, it was possible to observe an improvement in coating performance on a centimeter scale with the introduction of PAAm.

[0233] Furthermore, in secondary electron image (SEM) observation, in the silk cloth substrate and the filter paper substrate, when the amount of PAAm introduced was 0, the following state was established: in this state, plate-like crystals of PDA having a size of about 10 μm were aligned in a fiber manner, and when the amount of PAAm introduced was 1.3, the following state was established: in this state, spherical crystals having a size of about 1 μm to about 2 μm were entangled with the fiber (data not shown). By introducing PAAm, coating that is not easily peeled off and is physically stable is achieved.

[0234] (4-2) Increase in equipment area Subsequently, the spraying method was improved, and more various substrates (about 3 cm×3 cm, polyurethane, hard polyethylene, polypropylene, silk cloth, polyethylene fiber, and polystyrene) were coated with PAAm / PDA-p-Xy. Specifically, the operation of spraying the substrate three times with the spraying device and then drying the substrate with a cold air dryer was repeated about 6 or 7 times. The obtained PCDA / guest complex was solid-state photopolymerized by irradiation with UV light. A UV-LED lamp (CCS Inc., HLDL-120X30UV265-PSC, 265 nm) or a hand lamp (AS ONE, Handy UV Lamp SLUV-6, 254 nm) was used as the light source.

[0235] From the above-mentioned optimization, it was found that when the PCDA-p-Xy-PAAm precursor solution obtained by introducing 0.5 of p-Xy and 1 to 1.3 of PAAm relative to 1 of PCDA (molar ratio) was applied by spraying by the above-mentioned method, uniform increase in area of ​​any substrate could be performed. PAAm / PDA-p-Xy silk cloth substrates were manufactured under the same conditions, and color change behaviors due to increasing the temperature from 25°C to 115°C at every 5°C and cooling to 20°C at every 10°C were observed ( Fig.30 ). In addition, Fig.31 The graph of Δx obtained by normalizing the red intensity change Δx determined by image analysis is shown in FIG. st The relationship between temperature.

[0236] from Fig.30 Images and Fig.31 The graphs and images show that the fabricated PAAm / PDA-p-Xy fabric device shows a color change starting from about 80°C and reversibility up to about 110°C, and a uniform coating is obtained.

[0237] Explanation of reference numbers 10 Temperature imaging device, 11 substrate, 12 composite.

Claims

1. A temperature imaging device, comprising: Base material; as well as A composite having polyallylamine introduced between layers of poly-10,12-pentacosadiynoic acid, The composite is incorporated into or attached to the substrate.

2. The temperature imaging device according to claim 1, wherein: The temperature imaging device has an initial value of red intensity x before heating of 0.280 or more, and a value of a change amount Δx of the red intensity x when a color change is caused by heating to 100° C. is 0.025 or more.

3. A temperature imaging device, comprising: Base material; as well as A complex of poly-10,12-pentacosadiynoic acid, polyallylamine and an amine compound, The composite is incorporated into or attached to the substrate, Therein, at least a portion of the polyallylamine and / or the amine compound is introduced between the layers of the poly-10,12-pentacosadiynoic acid.

4. The temperature imaging device according to claim 1 or 3, wherein: The plurality of droplets of the composite are attached to the substrate in a dispersed state in a substantially spherical shape.

5. The temperature imaging device according to claim 1 or 3, wherein: The substrate is in sheet form, and Wherein, the temperature imaging device is a sheet-shaped device.

6. The temperature imaging device according to claim 1 or 3, wherein: The substrate includes woven fabric or non-woven fabric.

7. The temperature imaging device according to claim 1, wherein: The substrate is a sheet-like substrate having a length of 100 mm or more and a width of 100 mm or more.

8. The temperature imaging device according to claim 1, wherein: The temperature imaging device has a color change start temperature lower than 30°C and a color change end temperature higher than 80°C.

9. A method for estimating the specific heat of a liquid, the method comprising: heating the sealed container containing the liquid to a certain temperature; measuring a color change of the temperature imaging device of claim 1 or 3 attached to the container; calculating a specific heat equivalent value of the liquid based on a time period from the start of heating until the color change stops and an amount of change Δx of the red intensity x of the temperature imaging device from the start of heating until the color change stops; as well as The specific heat equivalent value of the liquid is substituted into a function formula of specific heat and specific heat equivalent value to calculate the specific heat of the liquid.

10. A method for checking temperature changes at a test site, the method comprising: Arranging the temperature imaging device according to claim 1 or 3 on the test site; as well as A color change of the temperature imaging device disposed on the test site after heating is detected.

11. The method according to claim 10, wherein: Detecting the color change includes detecting a color change of the temperature imaging device disposed on or near the affected part subjected to the heat treatment after heating with the energy device used for surgery.

12. An energy device for surgery, the energy device comprising: A coating is attached to the energy device, the coating comprising a composite having polyallylamine incorporated between layers of poly-10,12-pentacosadiynoic acid.

13. An energy device for surgery, the energy device comprising: A coating is attached to the energy device, the coating comprising a composite containing poly-10,12-pentacosadiynoic acid, polyallylamine and an amine compound, the composite having at least a portion of the polyallylamine and / or the amine compound introduced between layers of the poly-10,12-pentacosadiynoic acid.

14. A method for manufacturing a temperature imaging device, the method comprising: applying a composition containing 10,12-pentacosadiynoic acid, a polyallylamine having a unit represented by the following general formula (1), and a solvent to a substrate by spraying; removing the solvent; and The 10,12-pentacosadiynoic acid is polymerized to form a composite having the polyallylamine incorporated between layers of poly-10,12-pentacosadiynoic acid: , Here, n represents an integer.

15. A method for manufacturing a temperature imaging device, the method comprising: applying a composition containing 10,12-pentacosadiynoic acid, polyallylamine having a unit represented by the following general formula (1), an amine compound, and a solvent to a substrate by spraying; removing the solvent; as well as polymerizing 10,12-pentacosadiynoic acid to form a composite having at least a portion of the polyallylamine and / or the amine compound incorporated between layers of poly-10,12-pentacosadiynoic acid: , Here, n represents an integer.

16. The method according to claim 14 or 15, in, Forming the composite includes forming the composite such that the composite is attached to the substrate in a substantially spherical shape.

Citation Information

Patent Citations

  • Organ Model and Temperature Indicator Patch

    JP6801878B2